Private Law, Analytical Philosophy and the Modern Value of Wesley Newcomb Hohfeld: A Centennial Appraisal. (28th August 2018) - Barker, Kit
Abstract: Hohfeld is one of the best-known analytical philosophers to have written in the area of private law in western, common law legal systems in the twentieth century, but it is sometimes suggested that his scheme has had little impact on the law. One hundred years after his death, this article assesses the man and the impact of his work, noting a resurgence of interest in him amongst both commentators and courts. It suggests that there are two good reasons why his analytical philosophy is more relevant and useful today than ever – its potential to discipline and rationalise an increasingly insistent and ubiquitous rhetoric of rights; and the assistance it can provide in unpicking the complexity of the relationship between private law and the modern administrative state.